MONETARY POLICY (STUDY OF CONVENTIONAL AND ISLAMIC PERSPECTIVES) - Ika, Desi (Proceeding International Seminar of Islamic Studies, 2023)
As an important instrument in managing the modern economy, monetary policy is a key to success in stabilizing the country's economy. Where through the Central Bank, this policy regulates the supply and circulation of money in a country in such a way by designing financial variables such as the level of money supply and interest rates. The goal to be obtained is to maintain the stability of the value of money from various external and internal factors. Stability in the value of money is a reflection of stable prices which in turn can influence the achievement of a country's development goals such as meeting basic needs, equitable distribution, broad opportunities for employment, optimizing real economic growth and achieving economic stability. In principle, the goal of monetary policy in Islam is the same as conventional, namely the stability of currency values which leads to increased economic growth. However, the stability of currency values is intended to be carried out in ways that are in accordance with Allah's commands in the Qur'an. The frame of reference in monetary policy in the Islamic economy is the availability in terms of money stock, in addition to the objective it must be able to guarantee monetary developments that are not excessive but sufficient to make the most of the capacity of the economy in providing goods and services for the welfare of society as a whole.